On bifurcations of a system of cubic differential equations with an integrating multiplier singular along a second-order curve - Aleksandr Alekseev (Electronic Journal of Qualitative Theory of Differential Equations, 2015)
We establish necessary and sufficient conditions for existence of an integrating multiplier of a special form for systems of two cubic differential equations of the first order. We further study bifurcations of such systems with the change of parameters of their integrating multipliers.